Strict pure strategy Nash equilibria in large finite-player games - Guilherme Carmona; Konrad Podczeck (Theoretical Economics, 2021)
In the context of anonymous games (i.e., games where the payoff of a player is, apart from his/her own action, determined by the distribution of the actions made by the other players), we present a model in which, generically (in a precise sense), finite-player games have strict pure strategy Nash equilibria if the number of agents is large. A key feature of our model is that payoff functions have differentiability properties. A consequence of our existence result is that, in our model, equilibrium distributions of non-atomic games are asymptotically implementable by pure strategy Nash equilibria of large finite-player games.
Keywords: C72; 330; Large games; pure strategy; Nash equilibrium; generic property